P42 Movement Protein of Beet necrotic yellow vein virus Is Targeted by the Movement Proteins P13 and P15 to Punctate Bodies Associated with Plasmodesmata - M. Erhardt; M. Morant; C. Ritzenthaler; C. Stussi-Garaud; H. Guilley; K. Richards; G. Jonard; S. Bouzoubaa; D. Gilmer (Molecular Plant-Microbe Interactions, 2000)
Cell-to-cell movement of Beet necrotic yellow vein virus (BNYVV) is driven by a set of three movement proteins—P42, P13, and P15—organized into a triple gene block (TGB) on viral RNA 2. The first TGB protein, P42, has been fused to the green fluorescent protein (GFP) and fusion proteins between P42 and GFP were expressed from a BNYVV RNA 3-based replicon during virus infection. GFP-P42, in which the GFP was fused to the P42 N terminus, could drive viral cell-to-cell movement when the copy of the P42 gene on RNA 2 was disabled but the C-terminal fusion P42-GFP could not. Confocal microscopy of epidermal cells of Chenopodium quinoa near the leading edge of the infection revealed that GFP-P42 localized to punctate bodies apposed to the cell wall whereas free GFP, expressed from the replicon, was distributed uniformly throughout the cytoplasm. The punctate bodies sometimes appeared to traverse the cell wall or to form pairs of disconnected bodies on each side. The punctate bodies co-localized with callose, indicating that they are associated with plasmodesmata-rich regions such as pit fields. Point mutations in P42 that inhibited its ability to drive cell-to-cell movement also inhibited GFP-P42 punctate body formation. GFP-P42 punctate body formation was dependent on expression of P13 and P15 during the infection, indicating that these proteins act together or sequentially to localize P42 to the plasmodesmata.